MOBILE APPS, WEARABLES, AND eHEALTH LITERACY IN HEALTH-PROMOTING LIFESTYLES AMONG UNIVERSITY STUDENTS: AN INTEGRATIVE REVIEW - Szymczyk, Martyna; Pałubska, Jagoda; Muller, Oliwer; Szot, Anna; Szydełko, Dominik; Rosa, Katarzyna; Słoma, Agata; Danielczyk, Daria; Czyżewski, Wiktor; Malatyńska, Natalia (International Journal of Innovative Technologies in Social Science, 2026)
University students increasingly navigate health through digital environments, yet evidence on mobile applications, wearable devices, and eHealth literacy remains dispersed across separate literatures on physical activity, sleep, mental well-being, and online information behavior. This integrative review synthesized open-access evidence to examine how these elements jointly shape health-promoting lifestyles in university and adjacent young-adult populations. The analytical corpus comprised 13 publications published between 2018 and 2025, including systematic reviews, meta-analyses, a rapid review, broader youth-focused reviews, and 2 primary studies. Owing to heterogeneity in design, populations, and outcomes, the literature was synthesized narratively and interpreted through a student-centered pathway from digital access to lifestyle integration. Five themes emerged: digital information-seeking and source credibility; eHealth literacy and health competence; physical activity support; mental well-being and sleep; and usability, engagement, and implementation. The evidence indicates that eHealth literacy is linked to health knowledge, self-efficacy, preventive behavior, and, in longitudinal work, later health-promoting lifestyles. Digital tools show the most consistent benefits for physical activity, especially self-monitoring and step-related outcomes, while evidence for mental well-being and sleep is promising but methodologically uneven. Across domains, sustained benefit depends less on mere exposure to technology than on trust, interpretive capacity, low-burden design, and institutional fit. Mobile apps, wearables, and eHealth literacy should therefore be treated as interconnected components of student health promotion rather than as separate predictors. Future research should prioritize integrated multi-behavior interventions, standardized measures, and implementation strategies that are credible, equitable, and workable in everyday university life.